Bilateral in vivo neuromechanical properties of the triceps surae and achilles tendon in runners and triathletes - Jacques, T.; Bini, R.; Arndt, A. (Journal of Biomechanics, 2021)
Inter-limb differences in Achilles tendon mechanical, material and morphological properties have previously been described in non-athletes and attributed to the preferential use of a given limb. Achilles tendon overuse tendon injury generally initiate unilaterally and alters triceps surae activation and Achilles tendon properties. The investigation of inter-limb differences in muscle activation and tendon properties may provide directions for injury prevention in habitual runners. In this study triceps surae and Achilles tendon properties were investigated bilaterally in habitual runners during unilateral maximal isometric contractions. Morphological, mechanical and material Achilles tendon properties were assessed using isokinetic dynamometry, motion capture and ultrasonography while triceps surae activation strategies were assessed using electromyography. Lower limb preference was assessed for inter-limb comparisons using the Waterloo questionnaire. Zero and one-dimensional statistical analysis and Cohen`s d were employed to investigate possible inter-limb differences. Inter-limb associations in Achilles tendon properties and intra-limb associations between triceps surae activations were assessed using Pearson`s correlation coefficients. No differences were observed between the preferred and non-preferred limb in terms of triceps surae muscle activation amplitude and Achilles tendon properties. However, intra-limb association among triceps surae activation ratios were not identical between limbs. Runners and triathletes present similar Achilles tendons properties between limbs, and thus initial observations of unilateral changes in the Achilles tendon properties might be used as a strategy to prevent the onset of overuse tendon injury. The non-similar associations within activation ratios between limbs should be further explored since triceps surae activation strategies may alter loading of the Achilles tendon.